Quebra-cabeça tridimensional no Ensino Fundamental I: possibilidades de utilização interdisciplinar Matemática e Educação Física em uma perspectiva histórico-cultural - Barai, Alexandre (Universidade Federal de São Carlos, 2023)
The Rubik's Cube, popularly known as the magic cube, is a three-dimensional puzzle created by the Hungarian teacher Erno Rubik as didactic material to work with his students on the concept of three-dimensionality. However, building a cube on axes that allowed all six faces to rotate, he soon realized that he had created a puzzle. Current educational proposals encourage the use of games as a didactic resource in teaching skills and competences. In this way, intermediated by an interdisciplinary proposal Mathematics and Physical Education, this quali-quantitative study sought to use the magic cube as a complementary didactic material exploring its potentialities. And based on the Historical-cultural perspective with the support of content analysis and the IRAMUTEQ software, its main objective was to understand how the use of toys contributed to the development of logical-mathematical and cognitive-motor skills in students of the 5th grade of Elementary School I. Among the main results found, we can show that the use of toys encourages the appropriation of different skills and competences contained in educational proposals for Mathematics and Physical Education. In this sense, within the limitations of an exploratory-descriptive study, we point out that it is feasible to use the magic cube as a complementary didactic resource that stimulates the development of higher psychological functions, helping both in the appropriation of culture and systematized knowledge that permeated by the teaching intention favors the formation of scientific concepts by the students.
Three-dimensional puzzle in Elementary School: possibilities of interdisciplinary use in Mathematics and Physical Education in a historical-cultural perspective
Keywords: Cubo de Rubik; Ensino-aprendizagem; Interdisciplinaridade; Rubik's cube; Teaching-learning; Interdisciplinarity; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM